1992
DOI: 10.1080/15324989209381316
|View full text |Cite
|
Sign up to set email alerts
|

Influence of upper layer treatment of gel‐forming conditioner on water movement in sandy soils under sprinkler infiltration

Abstract: A laboratory sprinkler (rain) infiltration experiment was carried out on long stratified columns of sandy soil (Typic Torripsamments) packed to 1.50 g cm -3 bulk density to investigate the effect of gel-forming conditioner (Jalma) on wetting front advance Z, water distribution, and redistribution profiles under different sprinkler intensities I using a simple sprinkler simulator. Five concentrations of Jalma J, 0.0, 0.25, 0.50, 0.75, and 1.0% (on dry weight basis), were uniformly applied to the upper layer (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
4
9
0
Order By: Relevance
“…The addition of 0.1, 0.2, 0.3 and 0.4% of SHNC reduced the hydraulic conductivity by 16%, 36%, 48% and 63%, respectively. The decrease in hydraulic conductivity was in agreement with a former study by El-Shafei et al [ 25 ].…”
Section: Resultssupporting
confidence: 93%
“…The addition of 0.1, 0.2, 0.3 and 0.4% of SHNC reduced the hydraulic conductivity by 16%, 36%, 48% and 63%, respectively. The decrease in hydraulic conductivity was in agreement with a former study by El-Shafei et al [ 25 ].…”
Section: Resultssupporting
confidence: 93%
“…The enhancement in soil-polymer swelling and the clay dispersion influenced using deionized water during saturation could have caused reduction in pore space between soil accumulations and finally decreased K S amount (Levy et al, 2004). A similar decrease in K S with application of superabsorbent polymer was reported by El-Shafei et al (1992) and Andry et al (2009). The Ks relationship on soil temperature varied with the kind of superabsorbent used.…”
Section: Resultssupporting
confidence: 81%
“…The cross-linked polyacrylamides hold water up to 400 times their weight and release 95% of the retained water to growing plants Geoderma 187-188 (2012) 94-101 (Johnson, 1984a;Bowman and Evans, 1991). It was observed that the application of hydrogel to sandy soils improved water availability to plants by increasing the retention pores and reduced saturated hydraulic conductivity by decreasing the drainage pores (Al-Darby, 1996;Al-Omran and Al-Harbi, 1998;El-Hady and Abo-Sedera, 2006;El-Shafei et al, 1992;Kazanskii and Dubrovskii, 1992). Some studies, however, have reported contrasting results.…”
Section: Introductionmentioning
confidence: 93%